2020
DOI: 10.18778/1508-2008.23.01
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of National Business Cultures in the Countries of Central and Eastern Europe: the Basics for Improving International Entrepreneurship in Poland and Ukraine

Abstract: Based on the work of Hofstede, Trompenaars, Lewis, and Rapaille, the founders of the theory of national business cultures and comparative economic studies, the characteristics of corresponding scientific areas are identified: cross-cultural management, cross-cultural communications, and cross-cultural marketing, including their methodological and practical aspects. Using the classic measuring parameters of national business cultures (“Individualism,” “Power Distance,” “Masculinity,” “Uncertainty Avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…, 2021). Glinkowska-Krauze et al. (2020) state that Polish and Ukrainian business cultures, beyond geographic proximity, are a reliable basis for networks and mutually beneficial cooperation projects.…”
Section: Resultsmentioning
confidence: 99%
“…, 2021). Glinkowska-Krauze et al. (2020) state that Polish and Ukrainian business cultures, beyond geographic proximity, are a reliable basis for networks and mutually beneficial cooperation projects.…”
Section: Resultsmentioning
confidence: 99%
“…Krishnan (2017) studied the influence of cultural differences and showed that power distance was one of the predictors of technostress. Hofstede et al (2010) and Glinkowska-Krauze et al (2020) showed that Ukrainian and Belarussian people distinguish themselves with a higher power distance than for example Central and Western Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…Як представники економічної думки Великої Британії, зміст даної проблеми вони розглядали переважно з позицій менеджменту. Такий підхід став характерним для сучасної економічної науки західної (за виключенням Німеччини) та центрально-східної Європи, у тому числі -України [2][3][4][5][6].…”
unclassified